2018
DOI: 10.1039/c8cc01479e
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular hydrogen-bond activation for the addition of nucleophilic imines: 2-hydroxybenzophenone as a chemical auxiliary

Abstract: The addition of nucleophilic imines, using 2-hydroxybenzophenone as a chemical auxiliary, is presented. An intramolecular six-membered ring via hydrogen bonding that enhances the reactivity and selectivity is the key of this strategy, which is supported by DFT calculations and experimental trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Specifically, we were able to activate azamethylene imines to obtain pyrrolidines 11 and amino acid derivatives. 12 In addition, we were also able to increase the acidity of an imine derivative to achieve aza-Michael reactions to α,β-unsaturated aldehydes 13 (bottom, Scheme 1). We found that, in these reactions, not only the transition states (TS) were important, but also that the preassociation stage of the formed complexes (PAC) 14 was critical for the preorganization of the TS.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we were able to activate azamethylene imines to obtain pyrrolidines 11 and amino acid derivatives. 12 In addition, we were also able to increase the acidity of an imine derivative to achieve aza-Michael reactions to α,β-unsaturated aldehydes 13 (bottom, Scheme 1). We found that, in these reactions, not only the transition states (TS) were important, but also that the preassociation stage of the formed complexes (PAC) 14 was critical for the preorganization of the TS.…”
Section: Introductionmentioning
confidence: 99%
“…In pursuit of a more N-activated ketimine, 2-hydroxybenzophenone imine was described as a magnificent aminating reagent ( Scheme 12 ). 40 It was demonstrated that the hydroxyl group established a strong intramolecular H-bond with the nitrogen of the imine that increased the acidity of the NH proton. Thus, an alternative methodology for the asymmetric amination of enals using 2-hydroxybenzophenone imine derivatives as nucleophilic nitrogen sources was reported.…”
mentioning
confidence: 99%
“…Our research group has also made a special effort in the activation of C- and N-centered nucleophiles under organocatalytic conditions. The aforementioned acidity issues with respect to the use of monoactivated azomethine ylides in organocatalysis were resolved due to the glycine imine activation through an intramolecular hydrogen bond (Scheme ). , The presence of a hydroxyl group at the ortho position of the aromatic ring allowed for a H-bond with the iminic nitrogen, resulting in an acidity increase of the methylene hydrogens.…”
mentioning
confidence: 99%
“…10 In 2018, Alemán and co-workers successfully demonstrated an enantioselective aza-Michael addition of nucleophilic imines to enals using secondary amine catalyst 2 (Scheme 2b). 11 Trapping of the resultant β-imino aldehydes with a phosphorane gave the corresponding δ-imino esters in good yield and enantioselectivity. Notably, 2-hydroxybenzophenone imines showed increased reactivity and enantioselectivity compared with the parent benzophenone imine, attributed to an increase in acidity of the imine proton caused by intramolecular hydrogen bonding.…”
mentioning
confidence: 99%
“…Hydrogen bonding between the 2-hydroxy-substituent and the imine N serves to conformationally restrict this functionality and facilitate deprotonation. [11][12][13] Subsequent conjugate addition to the s-cis conformation of the a,b-unsaturated acyl isothiouronium 26 anti-to the stereodirecting phenyl substituent of the isothiourea catalyst generates the ammonium enolate intermediate 27. Proton transfer generates the b-imino acyl isothiouronium intermediate 28, with catalyst turnover facilitated by the aryloxide counterion to form the product and release the isothiourea catalyst BTM 7.…”
mentioning
confidence: 99%